2019
DOI: 10.1007/164_2019_209
|View full text |Cite
|
Sign up to set email alerts
|

NOP-Related Mechanisms in Substance Use Disorders

Abstract: Nociceptin/Orphanin FQ (N/OFQ) is a 17 amino acid peptide that was deorphanized in 1995 and has been widely studied since. The role of the N/OFQ system in drug abuse has attracted researchers' attention since its initial discovery. The first two scientific papers describing the effect of intracranial injection of N/OFQ appeared twenty years ago and reported efficacy of the peptide in attenuating alcohol intake whereas heroin self-admnistration was insensitive. Since then more than 100 scientific articles inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 169 publications
(246 reference statements)
1
25
0
5
Order By: Relevance
“…In addition, the tolerability and safety of BTRX-246040 once-daily dosing of 40 mg up to 8 weeks have been already demonstrated in clinical studies (Witkin et al, 2019). Collectively these features candidate BTRX-246040 as an essential pharmacological tool to further investigate the therapeutic potential of NOP antagonists as innovative drugs to treat depression (Gavioli and Calo, 2013), Parkinson's disease (Mercatelli et al, 2019), and possibly drug abuse 14 (Ciccocioppo et al, 2019) as well as to identify novel conditions/diseases where the blockade of the NOP receptor is associated with beneficial effects, including traumatic injuries of the central nervous system (Awwad et al, 2018;Sekine et al, 2018), post-traumatic stress disorders (Zhang et al, 2015;Genovese and Dobre, 2017), and sepsis (Carvalho et al, 2008;Williams et al, 2008). This article has not been copyedited and formatted.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, the tolerability and safety of BTRX-246040 once-daily dosing of 40 mg up to 8 weeks have been already demonstrated in clinical studies (Witkin et al, 2019). Collectively these features candidate BTRX-246040 as an essential pharmacological tool to further investigate the therapeutic potential of NOP antagonists as innovative drugs to treat depression (Gavioli and Calo, 2013), Parkinson's disease (Mercatelli et al, 2019), and possibly drug abuse 14 (Ciccocioppo et al, 2019) as well as to identify novel conditions/diseases where the blockade of the NOP receptor is associated with beneficial effects, including traumatic injuries of the central nervous system (Awwad et al, 2018;Sekine et al, 2018), post-traumatic stress disorders (Zhang et al, 2015;Genovese and Dobre, 2017), and sepsis (Carvalho et al, 2008;Williams et al, 2008). This article has not been copyedited and formatted.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, recent findings suggest that treatment of drug abuse might be an additional indication for NOP antagonists (Rorick-Kehn et al, 2016;Kallupi et al, 2017) (see for a detailed discussion of this topic (Ciccocioppo et al, 2019)).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies reported similar effects using NOP antagonists Ciccocioppo et al 2019). For instance, the NOP antagonist LY2940094 decreased voluntary ethanol intake in alcohol-preferring and -nonpreferring rats .…”
Section: Nociceptin/orphanin Fq and Alcohol-related Behaviormentioning
confidence: 72%
“…There is an ongoing debate on the mechanisms underlying similar effects using both NOP agonists and antagonists in decreasing the motivation for alcohol. One possible explanation is that NOP agonists may act through mechanisms involving desensitization of the system (Ciccocioppo et al 2019).…”
Section: Nociceptin/orphanin Fq and Alcohol-related Behaviormentioning
confidence: 99%
“…The putative therapeutic potential of NOP antagonists comes from studies in genetically modified NOP knockout rats. These animals self-administered significantly smaller amounts of alcohol, cocaine, and heroin, but showed unimpaired motivation for saccharin, which is a natural reward [ 238 ]. Hence, this group of compounds is more effective in preventing drug abuse [ 239 ] than NOP agonists and has promising utility for treating drug addiction.…”
Section: Anti-opioid Peptides: Potential Therapeutic Interestmentioning
confidence: 99%